1987
DOI: 10.2307/3586498
|View full text |Cite
|
Sign up to set email alerts
|

Content and Formal Schemata in ESL Reading

Abstract: This article reports the results of an experiment investigating the simultaneous effects on ESL reading comprehension of both culture-specific content schemata and formal schemata, as well as any potential interaction between them. In the study, highintermediate ESL students read, recalled, and answered questions about each of two texts. For each of two groups of readers (students of Muslim and Catholic/Spanish backgrounds), one text had culturally familiar content, the other culturally unfamiliar content. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
171
0
9

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(188 citation statements)
references
References 12 publications
8
171
0
9
Order By: Relevance
“…It is declared by many researchers that the cultural background of a reader influences his or her ability in understanding texts (Anderson, Sapiro, & Montague, 1977;Barnet, 1989;Carrell, 1987;Steffensen, Joag-Dev, & Anderson, 1979). This immersion allows them interpret the concepts in the TL because the learners are ijel.ccsenet.org Vol.…”
Section: Resultsmentioning
confidence: 99%
“…It is declared by many researchers that the cultural background of a reader influences his or her ability in understanding texts (Anderson, Sapiro, & Montague, 1977;Barnet, 1989;Carrell, 1987;Steffensen, Joag-Dev, & Anderson, 1979). This immersion allows them interpret the concepts in the TL because the learners are ijel.ccsenet.org Vol.…”
Section: Resultsmentioning
confidence: 99%
“…These well-developed activities, with explicit procedures to be followed, share the basic assumption that through proper questioning by teacher-initiated questions or student-generated questions, related background knowledge can be obtained (Anthony and Raphael, 1987). Carrell (1983Carrell ( , 1987 indicates that ESL/EFL teachers should work on minimising their students' reading difficulties by providing them with familiar content that includes relevant cultural information. The selected reading materials must activate students' relevant schemata which will then lead to a better understanding of what is being read.…”
Section: Activation Of Schemamentioning
confidence: 99%
“…In a study of the impact of both content and formal schemata, Johnson (1981) found that cultural information has more effect on reading comprehension than the syntactic structure of the text. Carrell (1987) investigated the concurrent effects of content and formal schemata and other potential interactions between them. She studied two high intermediate ESL learner groups, one containing Muslims and the other Catholics, and gave them two texts to read, one with culturally familiar content and the other with culturally unfamiliar content.…”
Section: Journal Of Language Teaching and Research 525mentioning
confidence: 99%